Increased Variability in Cold-Season Temperature since the 1930s in Subtropical China - Duan, Jianping; Zhang, Qi-Bin; Lv, Li-Xin (Journal of climate, 2013)
The recent increase in the frequency of winter cold extremes has received particular attention in light of the climate’s warming. Knowledge about changes in the frequency of winter cold extremes requires long-term climate data over large spatial scale. In this study, a temperature-sensitive tree-ring network consisting of 31 sampling sites collected from seven provinces in subtropical China was used to investigate the characteristics of cold-season temperature extremes during the past two centuries. The results show that the percentage of trees in a year that experienced an abnormal decrease in radial growth relative to the previous year can serve as an indicator of interannual change in January–March temperature in subtropical China. The frequency of extreme interannual decreases in cold-season temperature has increased since the 1930s. The change in cold-season temperature was significantly correlated with the intensity of the Siberian high, yet the correlation was much weaker in the period preceding the 1930s. The findings provide evidence of a frequency change in the occurrence of interannual cold-season temperature extremes in the past two centuries for subtropical China. Particularly, the pattern in the variation of cold-season temperature suggests a change in climate systems around the 1930s.